2009
DOI: 10.1088/0031-9155/54/8/015
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency noise from clinical linear accelerators

Abstract: There is a great deal of interest in image-guided radiotherapy (IGRT), and to advance the state of IGRT, an integrated linear accelerator-magnetic resonance (linac-MR) system has been proposed. Knowledge of the radiofrequency (RF) emissions near a linac is important for the design of appropriate RF shielding to facilitate the successful integration of these two devices. The frequency spectra of both electric and magnetic fields of RF emission are measured using commercially available measurement probes near th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…15 In the latter case, various studies exist which looked at the ability to take MRI images of phantoms while during linac irradiation 7,16 and investigated the effect of the radiation and RF noise from the linac on the gradient RF coils. 17,18 Recently, a proof-ofconcept study for tracking of a 1D pencil-beam navigator 19 and a study on tracking of phantom motion on 2D MRI images 20 have demonstrated that image acquisition is possible with MRI-linac prototypes incorporating a MLC.…”
Section: Introductionmentioning
confidence: 99%
“…15 In the latter case, various studies exist which looked at the ability to take MRI images of phantoms while during linac irradiation 7,16 and investigated the effect of the radiation and RF noise from the linac on the gradient RF coils. 17,18 Recently, a proof-ofconcept study for tracking of a 1D pencil-beam navigator 19 and a study on tracking of phantom motion on 2D MRI images 20 have demonstrated that image acquisition is possible with MRI-linac prototypes incorporating a MLC.…”
Section: Introductionmentioning
confidence: 99%
“…The whole setup was placed inside a Faraday RF Cage (Model FC-10, LBA Technologies, Greenville, NC) to remove any RF noise emanating from the linac's magnetron. 12,13 The detector was connected to a high speed low current amplifier (59-179 Edmund Optics) and all the measurements were taken with a nominal amplifier gain setting of 10 5 VA −1 . The radiation beam was focused on the detector through the RF cage, and the amplifier was not irradiated.…”
Section: Iiia Confirmation Of Buildup Methods For Ric Removalmentioning
confidence: 99%
“…9 in Ref. 8), which would not be the case if this signal was RF noise, as Burke et al 12 showed that the RF noise is essentially constant everywhere within the linac vault (see Fig. 5 in Ref.…”
Section: Iib Radiation Effect or Radiofrequency Interferencementioning
confidence: 97%
See 2 more Smart Citations